Biblioterapi untuk Meningkatkan Perkembangan Sosial pada Anak Prasekolah - Eka Adimayanti; Dewi Siyamti; Hapsari Windayanti (Jurnal Pengabdian Perawat, 2022)
Abstract Bibliotherapy is psychotherapy support through reading material to help someone who is experiencing personal problems or for other therapeutic purposes. Reading books are one of the media that teachers can use to stimulate children's social skills. Community Service Activities with the title "Bibliotherapy To Improve Social Development in Preschool Children". The purpose of this activity is to improve social development in preschool children. The method used is bibliotherapy through play therapy. The implementation of service is carried out for each class according to a predetermined schedule. Before we give the material to the students, we do apperception to each class teacher. After doing apperception with our class teacher, we continued the intervention. The first intervention is to examine the child's social skills with a questionnaire through the child's parents. Furthermore, bibliotherapy was carried out with different themes in each class. The final stage is to evaluate by assessing the child's social ability using a questionnaire on the child's social ability through parents. The results of monitoring social abilities in preschool children increased after playing therapy with the bibliotherapy method was carried out.